Korelasi Wabah â€œDemam Berdarah Dengue/ DBDâ€ dengan Tingkat Curah Hujan Rata â€“ Rata - Tristono, Tomi; Aji, Seno (Universitas Merdeka Madiun, 2020)
Abstractâ€” Along with the arrival of the rainy season in October 2018 - April 2019, the awareness of the emergence of Dengue Fever needs to be improved. Several methods for anticipation have been carried out, including by improving environmental cleanliness and holding mosquito spray or Fogging. These methods are considered to be ineffective in breaking the growth chain of Aedes Aegypti, which is the type of mosquito that most spreads Dengue Fever. To prevent infection, the World Health Organization (WHO) has also suggested controlling mosquito populations and protecting people from mosquito bites. This research uses the comparative method of Dengue Fever data in 2015, 2016, and 2017 of Jombang Regency. The data is correlated with average rainfall. Based on observations, the cases of Dengue Fever are repeated every year. The health office must socialize what dengue fever is, what are the symptoms, how to treat it if infected, and how to prevent it. The community needs to improve the cleanliness of the environment and be aware of water reservoirs or puddles if the rainy season. The presence of Jumantik cadres is very urgent and needed.Â Keywordsâ€”: Dengue Fever; rainy season; Aedes Aegypti; cleanliness of the environment.